Penguatan Kapasitas Digitalisasi UMKM Makanan Tradisional untuk Peningkatan Pendapatan Pedagang Sektor Informal - Sabilalo, Mahmudin A.; Hamid, Ahmad; Almana, Laode; Amirudin, Nazarudin H.; Tasrik, Tasrik (Universitas Pahlawan Tuanku Tambusai, 2025)
Traditional food-based Micro, Small, and Medium Enterprises (MSMEs) hold substantial potential for strengthening local economies and enhancing community welfare, particularly within the informal sector, including the Kelompok Usaha Bersama (KUBE) Amesiu located in Amesiu Village, Southeast Sulawesi. This cooperative consists of 20 productive housewives engaged in traditional food production. One of the main challenges faced by the group is the lack of digitalization, both in financial management (E-COUNT) and marketing (E-COMMERCE). The primary objective of this community engagement program was to strengthen the digital capacity of KUBE Amesiu through training on the use of E-COUNT and E-COMMERCE applications. The method employed was a technical guidance and mentoring approach (Bimbingan Teknis/Bintek). The results indicate that the implementation of the training on financial management using E-COUNT and online marketing through E-COMMERCE was well received, as evidenced by the full participation of all members. Prior to this program, KUBE members did not maintain systematic financial records of daily transactions and had not yet promoted or marketed their products widely, resulting in relatively low income levels.